The influence of adequate social support on adherence to HIV treatment on young adult females in a community in central Namibia - Ambayi, Julie (Stellenbosch : Stellenbosch University, 2011)
ENGLISH ABSTRACT: The study sought to establish the influence of adequate social support among young women in the age group 18 to 25 years, on adherence to HIV treatment in a community in Central Namibia. Bearing in mind that HIV comes with different degrees of stigmatisation in different communities, and the differences in how gender and age may affect coping mechanisms in the context of HIV infection, insight was deemed important. The aim of the study was to determine the extent to which social support influenced adherence to anti-retroviral treatment among young adult females infected with HIV, in order to improve adherence to treatment, treatment outcome as well as to provide guidance for effective health education campaigns. A quantitative research method was used which involved a survey. A written questionnaire with closed ended questions and a set number of responses was used in data collection, administered at selected HIV clinics by selected community counsellors in central Namibia. Qualitative research methods were also employed using interviews and focus group discussions. Interviews were conducted on selected men on HIV treatment attending the same clinics as the women involved in the questionnaires. In addition, focus group discussions were conducted with the healthcare providers from the selected clinics in central Namibia. The data from quantitative research was analysed using frequencies, averages, means, medians and basic correlations to derive the conclusion. Data from qualitative research methods was analysed using the coding system. The study showed that availability of adequate social support was uniquely associated with high levels of treatment adherence in young women infected with HIV. These results provide support for the continued psychosocial interventions in the management of HIV among those infected.